Spirulina platensis Extract Stabilizes Hepatic HIF-1α and Activates Caspase-3 in Aging Wistar Rat Liver - Reni Paramita; Febriana Catur Iswanti; Ninik Mudjihartini (Eureka Herba Indonesia, 2026)
Liver aging is accompanied by progressive hypoxia, impaired redox homeostasis, and dysregulated programmed cell death, for which safe complementary interventions are needed. Spirulina platensis (Arthrospira platensis), a marine cyanobacterium rich in the antioxidant phycobiliprotein C-phycocyanin, is widely used in Indonesian complementary medicine, yet its effect on the hepatic hypoxia–apoptosis–autophagy network across biological age is undefined. This in vivo study examined whether oral Spirulina extract modulates hepatic HIF-1α, caspase-3, and p62/SQSTM1 in young (12-week) and older (24-week) male Wistar rats. Animals (n=5 per group) received Spirulina extract 200 mg/kg body weight or aquabidest vehicle once daily for 29 days; livers were harvested and marker concentrations quantified by ELISA, with one-way ANOVA, Tukey HSD, η², Cohen’s d, and Pearson correlation. Spirulina increased hepatic HIF-1α by 60.0% in older rats (688.0±55.0 versus 430.0±40.0 pg/mg protein; p<0.001; Cohen’s d=5.37) but not in young rats (p=0.539). Caspase-3 rose 21.2% in older rats (145.68±12.80 versus 120.23±11.00 ng/mg protein; p=0.010; d=2.13), whereas p62 was unchanged across all groups (ANOVA p=0.903). HIF-1α and caspase-3 were strongly correlated (r=0.879; 95% CI 0.714–0.951; p<0.001). Spirulina also raised the hepatosomatic ratio and attenuated body-weight gain. These findings indicate that Spirulina engages the hepatic hypoxia–apoptosis axis in an age-dependent manner while preserving autophagy, providing mechanistic support for its use as a herbal hepatoprotective modality.